2016
DOI: 10.1080/00028487.2016.1159613
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Stream Condition on Habitat Diversity and Fish Assemblages in an Impaired Upper Snake River Basin Watershed

Abstract: Habitat diversity reflects the range of available habitats used by species with different niche requirements and, therefore, influences species diversity. Land use influences stream condition, and streams in poor condition are often wide, shallow, sediment‐laden channels with low instream habitat diversity. Our goal was to evaluate the effect of instream habitat diversity on fish species diversity, the effect of stream habitat condition on habitat diversity, and the effect of habitat diversity, stream conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 75 publications
0
9
0
2
Order By: Relevance
“…Habitat homogenization would lead to a decrease in species richness and fish diversity [64], and our study showed that fish richness and fish diversity were significantly affected by habitat type. Low-head weirs are widely distributed in upstream sections of Lijiang River, which might play a substantial role in reshaping habitats in terms of water depth, velocity, substratum composition and the transition between free-flowing water and interstitial zone, resulting in habitat homogenization on a small scale [65,66].…”
Section: Discussionmentioning
confidence: 59%
“…Habitat homogenization would lead to a decrease in species richness and fish diversity [64], and our study showed that fish richness and fish diversity were significantly affected by habitat type. Low-head weirs are widely distributed in upstream sections of Lijiang River, which might play a substantial role in reshaping habitats in terms of water depth, velocity, substratum composition and the transition between free-flowing water and interstitial zone, resulting in habitat homogenization on a small scale [65,66].…”
Section: Discussionmentioning
confidence: 59%
“…The contribution of local predictors emphasises the importance of maintaining habitat characteristics similar to least impacted conditions for the conservation of stream fish assemblages in the Cerrado (Casatti, Ferreira & Carvalho, ; Ferreira, Silva, Gonçalves & Petrere, ; Walrath, Dauwalter & Reinke, ). Coarse substrate, flow velocity and leaf litter accumulations were particularly important instream characteristics related to fish assemblage composition in the final RDA model.…”
Section: Discussionmentioning
confidence: 99%
“…The contribution of local predictors emphasises the importance of maintaining habitat characteristics similar to least impacted conditions for the conservation of stream fish assemblages in the Cerrado (Casatti, Ferreira & Carvalho, 2009;Ferreira, Silva, Gonçalves & Petrere, 2014;Walrath, Dauwalter & Reinke, 2016 (Carvalho, Fidelis, Arruda, Galuch & Zuanon, 2013;Casatti et al, 2009). On the other hand, impaired streams without riparian vegetation are more susceptible to siltation due to sediment input from adjacent areas, causing homogenisation of stream bottom habitats (Bojsen & Barriga, 2002;Dauwalter, Wenger & Gardner, 2014;Growns, Gehrke, Astles & Pol Lard, 2003).…”
Section: Relative Importance Of Local and Landscape Environmental Vmentioning
confidence: 99%
“…Livestock tend to congregate in these systems, due to increased water and forage availability [8]. Improper grazing management has been shown to reduce vegetation, leading to destabilized streambanks and erosion [9,10]. Over-grazing can also decrease leaf area, nutrient stocks, photosynthetic capability, reproductive success, and vegetative growth [11][12][13].…”
Section: Introductionmentioning
confidence: 99%